2013
DOI: 10.5487/tr.2013.29.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Arsenic Concentrations and their Associated Factors in Korean Adults

Abstract: Arsenic (As) is a well-known human carcinogen and its dietary exposure has been found to be the major route of entry into general population. This study was performed to assess the body levels of As and their associated factors in Korean adults by analyzing total As in urine. Urine and blood samples were collected from 580 adults aged 20 years and older, who had not been exposed to As occupationally. Demographic information was collected with the help of a standard questionnaire, including age, smoking, alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
2
17
3
1
Order By: Relevance
“…While, Bae et al (2013) did not find an association between alcohol consumption and arsenic levels, in this study, amount of alcohol consumed during the last 24 h was found to be associated with elevated levels of UAS, UDMA, as well as UAB (Table 5). On the other hand, Aguilera et al (2008) did report a dose response relationship between alcohol consumption and arsenic levels among adults living in Spain.…”
Section: Impact Of Alcohol Consumptioncontrasting
confidence: 65%
See 4 more Smart Citations
“…While, Bae et al (2013) did not find an association between alcohol consumption and arsenic levels, in this study, amount of alcohol consumed during the last 24 h was found to be associated with elevated levels of UAS, UDMA, as well as UAB (Table 5). On the other hand, Aguilera et al (2008) did report a dose response relationship between alcohol consumption and arsenic levels among adults living in Spain.…”
Section: Impact Of Alcohol Consumptioncontrasting
confidence: 65%
“…Bae et al (2013) found Korean men aged 20 years and over to have higher urinary arsenic levels than females. In this study also, males aged ≥12 years were found to have higher adjusted UDMA levels than females ( (2014) found female nonsmokers to have higher adjusted levels than male nonsmokers for adults aged ≥20 years.…”
Section: Impact Of Gender and Race/ethnicitymentioning
confidence: 94%
See 3 more Smart Citations